Pengaruh Moda Transportasi Darat Terhadap Kelancaran Bongkar Muat - Sevia Dwi Astuti; Tiara Nur Angraini; Ikram Maulana Firdaus; Taufik Nurochman; Siti Sahara; Kencana Verawati (Peneliti.net, 2023)
Ports play an important role in facilitating international trade and commerce. They provide a platform for the exchange of goods and services between countries, enabling businesses to extend their reach beyond their country's borders. Ports serve as transportation hubs, connecting various modes of transportation, including ships, trucks, and trains. They also provide facilities for storage and handling of goods, making it easier for businesses to manage their inventory and supply chain. This study aims to determine the effect of the Mode of Land Transportation on the Smooth Loading and Unloading because there are still frequent traffic jams at a number of road points that lead to the Port of Tanjung Priok which results in hindering the smooth loading and unloading process, so that it can reduce the productivity of the company. According to the results and discussion of the efforts to optimize the impact of land transportation modes on the smooth loading and unloading are improving infrastructure, improving TKBM performance, imposing sanctions, and optimizing CY.